2019
DOI: 10.1021/acs.langmuir.8b03951
|View full text |Cite
|
Sign up to set email alerts
|

ReaxFF MD Simulations of Peptide-Grafted Gold Nanoparticles

Abstract: Functionalized gold nanoparticles have critical applications in biodetection with surface-enhanced Raman spectrum and drug delivery. In this study, reactive force field molecular dynamics simulations were performed to study gold nanoparticles, which are modified with different short-chain peptides consisting of amino acid residues of cysteine and glycine in different grafting densities in the aqueous environment. Our study showed slight facet-dependent peptide adsorption on a gold nanoparticle with the 3 nm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…This method is the simplest approach for functionalizing the surface of NDS with peptides [31,32]. This method has been extensively employed for preparing cysteine (Cys, C)-containing peptides functionalized AuNPs owing to the presence of the thiol group of cycteine, which is capable of forming a strong S-Au covalent bond with the surface of AuNPs [33][34][35][36][37]. Lévy et al demonstrated that the cysteine-alanine-leucine-asparagineasparagine (CALNN) pentapeptide is capable of converting citrate-capped AuNPs to stable and water-soluble AuNPs equipped with chemical features similar to proteins [37].…”
Section: Ligand Exchange Methodsmentioning
confidence: 99%
“…This method is the simplest approach for functionalizing the surface of NDS with peptides [31,32]. This method has been extensively employed for preparing cysteine (Cys, C)-containing peptides functionalized AuNPs owing to the presence of the thiol group of cycteine, which is capable of forming a strong S-Au covalent bond with the surface of AuNPs [33][34][35][36][37]. Lévy et al demonstrated that the cysteine-alanine-leucine-asparagineasparagine (CALNN) pentapeptide is capable of converting citrate-capped AuNPs to stable and water-soluble AuNPs equipped with chemical features similar to proteins [37].…”
Section: Ligand Exchange Methodsmentioning
confidence: 99%
“…Generally, the NPs were firstly produced by the hydrothermal or solvothermal approaches [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. The as-prepared NPs were then modified with different peptides to achieve different functionalities for further applications.…”
Section: Synthesis Of Peptide Functionalized Nanoparticlesmentioning
confidence: 99%
“…The ligand exchange method is the simplest strategy for preparing peptide functionalized NPs, which essentially involves displacement of original ligand on NP surface by a specific peptide ligand and/or a mixture of peptide ligand [ 40 , 41 ]. Cysteine (Cys, C)-containing peptides have been used successfully to synthesize various peptide functionalized AuNPs by ligand exchange method because the thiol group (−HS) of cysteine can form strong S-Au covalent bond with surface Au atoms of AuNPs [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. As early as 2004, Lévy and colleagues demonstrated that the pentapeptide, CALNN, can convert citrate-capped AuNPs into extremely stable, water-soluble AuNPs with some chemical properties analogous to those of proteins [ 42 ].…”
Section: Synthesis Of Peptide Functionalized Nanoparticlesmentioning
confidence: 99%
“…2021, 22, 3624 2 of 17 gold nanoparticles (NP) by means of atomistic simulations. From simulations, observed experimental evidences have been interpreted as the result of changes in peptide conformation due to the gold nanocluster [22], or to the presence of water molecules and structured sulphur interfacial atoms within the peptide monolayer [23], or the protonation/deprotonation state of peptide-capped gold functional groups [24]. It also has been shown that the self-assembly of bio-functionalized gold NPs [25] can be affected by the flexibility, stability and conjugation dynamics of the peptide functional groups which, in turn, is a function of the peptide length.…”
Section: Introductionmentioning
confidence: 99%